(3YLGFH GdCNHGQ Yf eUQ GdCeUGQs - (3eYQha Hf CMeOs
(3ChdgG (B:s
(3hHYO, agPg faMGJ bOS JfSeJ , hRgQGJ CfS JHSeJ s
(3BNQgG (B:s
(3NGJeI aj OYhGJ eCKhQI , LeYJgG ef YOI CHhGH hUdi Gddg Ydi SjOfG eMeO , hYdi Bdg hUMHg hSde s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B285 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQjI (B((320 (3CHGXI(B) 6620) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdJGQjNs